The causes for inefficacy of antihelicobacter therapy - I. V. Mayev; Yu. A. Kucheryavyy; D. N. Andreyev (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To summarize and analyze main causative factors determining inefficacy of modern algorithms of antihelicobacter therapy.Key points. Efficacy of eradication therapy (ET) can depend on a lot of factors which generally can be divided in three main groups in relation to origin: factors determined by microorganism (bacteria); factors determined by macroorganism (patient); the factors determined by doctor. Hence, in clinical practice cases a single patient may have combination of several independent factors determining failure of provided treatment.Conclusion. Efficacy ET depends upon wide spectrum of heterogeneous mechanisms. For the present moment, the primary factor determining inefficacy of treatment, is increase of H. pylori antibiotic resistance to the basic drugs, applied in modes of the first line of ET.